Techne meets Metis: Knowledge and practices for tick control in Laikipia County, Kenya - Mutavi, Faith; Aarts, N.; Passen, A. van; Heitkönig, I.; Wieland, Barbara (Informa UK Limited, 2018)
Prevention of tick borne diseases is often through tick control practices. This article diagnoses tick control practices, knowledge underlying these practices and how knowledge is shared at the wildlife-livestock interface in Laikipia County, Kenya. It identifies diverse land use and tick control practices by different land and livestock owners from a scientific knowledge-based (techne) and context driven experiential knowledge-based (metis) perspective.